Funding for research on cryptococcal disease: an analysis based on the G-finder report - Iraine Duarte; Marcio L. Rodrigues (IMA Fungus)
Abstract Members of the genus Cryptococcus are the causative agents of cryptococcal meningitis, a disease mainly associated with HIV-induced immunosuppression. Patients with cryptococcal meningitis are at a serious risk of death. Most patients suffering from cryptococcosis belong to neglected populations. With reduced support for research, new therapies are unlikely to emerge. In this essay, we used the Policy Cures/G-finder platform as a reference database for funding research on cryptococcal disease. Funding for cryptococcal research started being tracked by G-finder in 2013 and has continued to appear in the annual reports ever since. In total, 15 institutions were reported as major funders for research on cryptococcal disease over the years. The US National Institutes of Health (NIH) was the main funder, followed by the UK's Wellcome Trust. The annual analysis suggested slow yearly growth in funding from 2013 to 2021. The development of new tools to prevent and fight cryptococcal disease is urgent but requires improved funding.